Forced marriage of people with learning disabilities: a human rights issue - Clawson, Rachael; Fyson, Rachel (Taylor & Francis, 2017)
This paper reports some of the findings of an exploratory study which sought to better understand the demographics of forced marriage of people with learning disabilities and the contexts in which such marriages may occur. It was found that forced marriages of people with and without learning disabilities showed broad similarities in relation to ethnicity, some differences in terms of age and substantial differences in terms of gender. Men and women with learning disabilities are equally likely to be victims of forced marriage. The reasons for people with learning disabilities being forced to marry are most often associated with a desire on the part of families to secure permanent care, but can also be associated with cultural (mis)understandings of the nature of disability. These findings are contextualised by considering the relationship between forced marriage, human rights and learning disability.